Clinical characteristics and factors associated with recurrence and long-term prognosis in patients with MOGAD - Sun, Wenlin; Xie, Yinyin; Han, Aoya; Zhou, Xinru; Zhang, Shijie; Xie, Yi; Xie, Nanchang (Frontiers in Immunology, 2025)
ObjectiveTo describe the clinical features, treatment, and prognostic factors affecting recurrence and long-term adverse outcomes of myelin oligodendrocyte antibody-associated disease (MOGAD).MethodsIn this retrospective cohort study, the records of patients diagnosed with MOGAD at Zhengzhou University First Affiliated Hospital between January 2018 and March 2023 were analyzed, and factors associated with recurrence and poor long-term prognosis were identified using logistic regression.ResultsOf the 91 patients, 69 (76%) were new cases, 39 (43%) were female, and 47 (52%) were children (<18 years). Clinical manifestations included optic neuritis (ON) in 13 (14%), transverse myelitis (TM) in 14 (15%), brain disease in 37 (41%), and mixed encephalomyelitis in 27 (30%). The prevalence of acute disseminated encephalomyelitis (ADEM) was significantly higher in children than in adults (43% versus 18%, p = 0.012), whereas the prevalence of TM was significantly higher in adults (30% versus 2%, p < 0.001). Combined steroid and intravenous immunoglobulin (IVIG) treatment during hospitalization was more frequent in children than in adults (36% versus 11%, p = 0.006), and children had a better short-term prognosis than that in adults at discharge (median [interquartile range (IQR)]) Expanded Disability Status Scale [EDSS]: 1 [0–1] versus 2 [0–4.75], p = 0.007; Modified Rankin Score [mRS]: 1 [0–1] versus 1 [0–2], p = 0.006). Visual impairment was a risk factor for recurrence (odds ratio [OR]: 4.22, 95% confidence interval [CI]: 1.24–14.38, p = 0.022). A higher EDSS score at discharge (OR: 5.05, 95% CI: 1.27–20.07, p = 0.021)and more previous episodes (OR: 9.24, 95% CI: 1.35–63.10, p = 0.023), were associated with a poor long-term prognosis; whereas steroid therapy for >5 weeks at first diagnosis (OR: 0.001, 95% CI: 0.00–0.33, p = 0.019) and type I isoelectric focusing pattern (OR: 0.004, 95% CI: 0.00–0.402, p = 0.043) were associated with favorable long-term prognosis.ConclusionAfter the first episode, steroid maintenance for an appropriate period following discharge is important for achieving a favorable long-term prognosis, particularly in patients with a high EDSS score at discharge and those at a heightened risk of recurrence.